MODELING AND ANALYSIS OF THE CHARACTERISTICS OF MULTICHANNEL AND MULTI-NODE COMPUTER NETWORKS WITH PRIORITY SERVICE - Huseynov, Zakir Nasib; Mammadov, Mahil Isa; Ismayilov, Togrul Atabay (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2023)
The subject of the research is modeling and analysis of the characteristics of multichannel and multi-node computer networks with priority services. The work is devoted to the study of the qualitative indicators of the functioning of computer networks with priority service. In this work, mathematical models are developed that make it possible to assess the quality of functioning of modern computer networks, taking into account the number of channels, waiting places in network nodes and the number of network nodes. The proposed methods for calculating the probability of failures and the probability of timely delivery of a stream of requests make it possible to determine the real values of the qualitative indicators of the functioning of computer networks and are suitable for both designed and operating computer networks. The proposed technique makes it possible to determine the number of packets in the queue and the optimal amount of buffer memory in computer network nodes.